Underpriced IPOs in the US: Influence of sectors and VCs in IPOs performance and price - Alves, André Jorge Vicente (2021)
Underpricing is present in most of the initial public offerings, which tend to underperform in the course of time. For that reason, I develop regression models that evaluate the impact and importance of factors such as offer price, closing price, underpricing, type of sector, type of capital structure and stock exchange in the initial public offerings first day level of underpricing, 3-year, 3-year to 5-year and 5-year share performance and 3-year and 5-year share price, after the issuance. Furthermore, these models are tested on a sample of initial public offerings listed between 2000 to 2014. Hereupon, I find that venture capitalist backed initial public offerings have a positive relationship with first-day underpricing, 3-year and 5-year performance and share price, whereas the offer price and closing price have with the 3-year and 5-year share price. The Information Technology, Communication Services and Consumer Discretionary sectors underprice more in the first day than the others.